A gendered perspective on Learning to Labour. Issue 2 (15th March 2017) - Höpfl, Heather; Hamilton, Lindsay; Brannan, Matthew
Abstract : This paper presents an auto-ethnographic study of the personal experience of learning to labour. Heather Hopfl reflects on the prospects and opportunities presented to her as part of her life and experiences of learning to labour during the same period as Willis's study: which, of course, is specific to young men. Consequently, the paper reflects on the implications of class location and life chances, on the social engineering experimentation of the 1950s and 60s, on the options presented by a grammar school education and on the impossibility of return occasioned by such opportunities. It discusses the escape routes open to some but closed to many.